A CASE REPORT OF DIFFICULT DIAGNOSIS IN THE PATIENT WITH LARYNGEAL CANCER - D. V. Gavrilyuk; M. V. Avdeenko; R. A. Zukov; S. Yu. Chizhevskaya (Сибирский онкологический журнал, 2016)
We present a case of the difficult morphological verification and ambiguous interpretation of immunohistochemical examination of cervical lymph nodes metastases from unknown primary tumor with late clinical diagnosis of laryngeal cancer. The detailed morphological features of metastases in cervical lymph nodes from unknown primary tumor were described. External beam radiotherapy to regional cervical lymph nodes in patients with unknown primary tumor can result in reduction and even regression of the primary tumor, thus making the detection of the primary tumor difficult. The time of diagnosis of the primary laryngeal tumor was 2 year and 4 months.